THE EXAMINATION OF BALL SKILL DEVELOPMENT IN YOUTH FOOTBALL PLAYERS - Haraszti, Patrik Zoltán; Lente, Lajos; Pucsok, József Márton; Lenténé Puskás, Andrea (Stadium - Hungarian Journal of Sport Sciences, 2024)
In modern football, in addition to advanced physical and mental abilities, players must have excellent technical skills. Coaches must emphasize the development of ball skills during youth training that will enable athletes to execute technical elements accurately and precisely, even at a fast game pace. The present research investigated the significance and effects of ball skill development among youth football players. The study focuses on the role and importance of technical elements in football, implementing the Coerver training method. Material and methods: The U11, U13, and U14 youth teams of Loki Focisuli Debrecen KSE participated in the study. We examined the effect of a 14-week training program on ball skills. We implemented sport-specific tests to assess these technical skills. Fourteen weeks later, we conducted the second measurement under the same conditions. Results and conclusion: The study confirmed that youth football players may improve ball skills with the help of a 14-week training program based on Coerver’s training method. The most significant improvement was measured in the U11 age group.